Behavioural adjustments in the social associations of a precocial shorebird mediate the costs and benefits of grouping decisions. Issue 4 (24th February 2022) - Wilde, Luke R.; Swift, Rose J.; Senner, Nathan R.
Abstract: Animals weigh multiple costs and benefits when making grouping decisions. The cost‐avoidance grouping framework proposes that group density, information quality and risk affect an individual's preference for con or heterospecific groups. However, this assumes the cost–benefit balance of a particular grouping is constant spatiotemporally, which may not always be true. Investigating how spatiotemporal context influences grouping choices is therefore key to understanding how animals contend with changing conditions. Changes in body size during development lead to variable conditions for individuals over short time‐scales that can influence their ecological interactions. Hudsonian godwits Limosa haemastica, for instance, form a protective nesting association with a major predator of young godwit chicks, colonial short‐billed gulls Larus brachyrhynchus . Godwit broods may avoid areas of higher gull densities when chicks are susceptible to gull predation but likely experience higher risk from alternative predators as a result. Associating with conspecifics could allow godwits to buffer these costs but requires enough other broods with whom to group. To determine how age‐dependent predation risk and conspecific density influence godwit grouping behaviours, we first quantified the time‐dependent effects of con‐ and heterospecific interactions on the mortality risk for godwit chicks throughout development. We then determined how godwit density and chick age affected their associations with con‐ and heterospecific. We found that younger godwit chicks' survival improved with closer association with conspecifics, earlier hatch dates and lower gull densities, whereas older chicks survived better with earlier hatch dates, though this effect was less clear. Concomitantly, godwit broods avoided gulls early in development and when godwit densities were high but maintained loose associations with conspecifics throughout development. We identified how individuals can optimally shift with whom they group according to risks that vary spatially and temporally. Investigating the effects of a species' ecological interactions across spatiotemporal contexts in this way can shed light on how animals adjust their associations according to the costs and benefits of each association. Abstract : Using precocial shorebird chicks, Hudsonian godwits, and a major chick predator, short‐billed gulls, the authors show the adjustment in species' associations according to changes in stage‐dependent predation risk can be a behavioral method to avoid costs of sometimes dangerous interactions. Updating the framework around animal grouping decisions to account for shifting trade‐offs in species' associations will improve predictions about community structure.